Solar-thermoelectric mobile storage system integrated with electric vehicles for reducing postharvest and microbial losses in agro produce transportation - Lalith Pankaj Raj Nadimuthu; Kirubakaran Victor; Mohit Bajaj; Vojtech Blazek; Lukas Prokop (Scientific Reports)
Abstract Agriculture constitutes a foundational pillar of the Indian economy, contributing nearly 18% to the national Gross Domestic Product (GDP) and ranking second globally in horticultural output. Beyond its economic significance, the sector underpins rural employment, food security, and a wide range of agro-based downstream industries. Despite these strengths, Indian agriculture continues to encounter critical bottlenecks—most notably, post-harvest losses in fruits, which are estimated to range between 6.02% and 15.05%. These losses are predominantly attributed to the lack of accessible and decentralized cold storage infrastructure. Maintaining optimal temperature and humidity levels throughout the cold chain is essential to curtail physicochemical degradation and suppress microbial growth, both of which substantially diminish the quality and shelf life of perishable produce. This study introduces a solar photovoltaic (PV)-driven micro cold storage (MCS) system, specifically engineered for seamless integration with electric vehicles (EVs) to effectively mitigate post-harvest losses in perishable agricultural commodities. The research undertakes a comprehensive performance evaluation of the proposed system, which employs a thermoelectric cooling mechanism powered entirely by solar energy. Emphasis is placed on assessing the system’s thermal, electrical, and microbial preservation capabilities under both static and dynamic operational conditions, highlighting its potential for sustainable and mobile cold chain applications in rural agricultural contexts. The system comprises a 100 Wp polycrystalline solar photovoltaic (PV) module, which supplies power to a 12 V/6A shunt-configured thermoelectric cooler with a 12 L storage capacity via a 12 V/8A solar charge controller. Functioning as an off-grid refrigeration unit, the system is supported by a 12 V/40Ah battery energy storage system. The experimental analysis focuses on assessing the shelf life of Vitis vinifera (grapes) over a one-week storage period by measuring physiological loss in weight (PLW) as the key parameter for evaluating storage efficiency. The refrigeration chamber maintains a controlled temperature range of + 2 °C to + 8 °C. Findings indicate a controlled weight reduction of up to 87.6% in refrigerated grapes compared to those stored under ambient conditions. Also, the system’s performance to maintain proper storage conditions during short-distance transportation (six hours) is evaluated to demonstrate effective farm-to-market connectivity through electric vehicle utilization. The study evaluates the electrical and thermal performance of a system for renewable energy-integrated electric vehicle applications. It also investigates the effectiveness of a solar-powered modified controlled storage (MCS) system in preventing microbial growth and maintaining agro-produce quality during storage and transport. The microbial load, including bacterial, fungal, and yeast populations, was quantified using colony-forming unit (CFU) counts per millilitre to evaluate the system’s efficacy in ensuring food safety. The findings underscore the environmental sustainability and practical applicability of the MCS system in the preservation of perishable agricultural produce. By enabling access to affordable, reliable, and renewable energy sources, the system directly contributes to the achievement of Sustainable Development Goal (SDG) 7, while simultaneously addressing food waste reduction and improving the efficiency and resilience of agro-supply chains.